Effective Methods of Training Vocational Education Specialists in Higher Education Institutions - Gulnaz Mirzaxmatovna, Anarkulova; Gulbahor Adiljanovna, Ruzimatova; Nilufar Egamberganovna, Raximova; Malika Mominovna, Parpiyeva; Farrukh Fattoevich, Salomov (International Journal of Psychosocial Rehabilitation, 2020)
This article is devoted to the problem of pedagogical technologies as one of the factors affecting the quality of training of specialists in higher educational institutions. The article discloses the theory and methodological requirements of pedagogical technologies, the conceptual foundations of pedagogical technologies, and the concepts of pedagogical technologies in three aspects. And also the essence of the role in the training of specialists of personality-oriented, subject-oriented pedagogical technologies is examined.